Natural map derivation algorithm - haskell

This Reddit post by Edward Kmett provides a constructive definition of a natural map, the one from the free theorem for fmap (which I read in yet another Edward Kmett's post):
For given f, g, h and k, such that f . g = h . k: $map f . fmap g = fmap h . $map k, where $map is the natural map for the given constructor.
I do not fully understand the algorithm. Let us approach it step-by-step:
We can define a "natural map" by induction over any particular concrete choice of F you give.
Ultimately any such ADT is made out of sums, products, (->)'s, 1s, 0s, a's, invocations of other
functors, etc.
Consider:
data Smth a = A a a a | B a (Maybe a) | U | Z Void deriving ...
No arrows. Let us see how fmap (which I reckon to be the natural choice for any ADT without (->)s in it) would operate here:
instance Functor Smth where
fmap xy (A x x1 x2) = A (xy x) (xy x1) (xy x2)
fmap xy (B x xPlus1) = B (xy x) (fmap xy xPlus1)
-- One can pattern-match 'xPlus1' as 'Just x1' and 'Nothing'.
-- From my point of view, 'fmap' suits better here. Reasons below.
fmap _xy U = U
fmap _xy (Z z) = absurd z
Which seems natural. To put this more formally, we apply xy to every x, apply fmap xy to every T x, where T is a Functor, we leave every unit unchanged, and we pass every Void onto absurd. This works for recursive definitions too!
data Lst a = Unit | Prepend a (Lst a) deriving ...
instance Functor Lst where
fmap xy Unit = Unit
fmap xy (Prepend x lstX) = Prepend (xy x) (fmap xy lstX)
And for the non-inductive types:(Detailed explanation in this answer under the linked post.)
Graph a = Node a [Graph a]
instance Functor Graph where
fmap xy (Node x children) = Node (xy x) (fmap (fmap xy) children)
This part is clear.
When we allow (->) we now have the first thing that mixes variance up. The left-hand type argument of (->) is in contravariant position, the right-hand side is in covariant position. So you need to track the final type variable through the entire ADT and see if it occurs in positive and/or negative position.
Now we include (->)s. Let us try to keep this induction going:
We somehow derived natural maps for T a and S a. Thus, we want to consider the following:
data T2S a = T2S (T a -> S a)
instance ?Class? T2S where
?map? ?? (T2S tx2sx) = T2S $ \ ty -> ???
And I believe this to be the point where we start choosing. We have the following options:
(Phantom) a occurs neither in T nor in S. a in T2S is phantom, thus, we can implement both fmap and contramap as const phantom.
(Covariant) a occurs in S a and does not occur in T a. Thus, this something among the lines of ReaderT with S a (which does not actually depend on a) as environment, which substitutes ?Class? with Functor, ?map? with fmap, ???, ?? with xy with:
let tx = phantom ty
sx = tx2sx tx
sy = fmap xy sx
in sy
(Contravariant) a occurs in T a and does not occur in S a. I do not see a way to make this thing a covariant functor, so we implement a Contravariant instance here, which substitutes ?map? with contramap, ?? with yx, ??? with:
let tx = fmap yx ty
sx = tx2sx tx
sy = phantom sx
in sy
(Invariant) a occurs both in T a and S a. We can no longer use phantom, which came in quite handy. There is a module Data.Functor.Invariant by Edward Kmett. It provides the following class with a map:
class Invariant f where
invmap :: (a -> b) -> (b -> a) -> f a -> f b
-- and some generic stuff...
And yet, I cannot see a way to turn this into something we can pluf into the free theorem for fmap - the type requires an additional function-argument, which we can't brush off as id or something. Anyway, we put invmap instead of ?map?, xy yx instead of ??, and the following instead of ???:
let tx = fmap yx ty
sx = tx2sx tx
sy = fmap xy sx
in sy
So, is my understanding of such an algorithm correct? If so, how are we to properly process the Invariant case?

I think your algorithm is too complex, because you are trying to write one algorithm. Writing two algorithms instead makes things much simpler. One algorithm will build the natural fmap, and the other will build the natural contramap. BUT both algorithms need to be nondeterministic in the following sense: there will be types where they cannot succeed, and so do not return an implementation; and there will be types where there are multiple ways they can succeed, but they're all equivalent.
To start, let's carefully define what it means to be a parameterized type. Here's the different kinds of parameterized types we can have:
F ::= F + F'
| F * F'
| F -> F'
| F . F'
| Id
| Const X
In Const X, the X ranges over all concrete, non-parameterized types, like Int and Bool and so forth. And here's their interpretation, i.e. the concrete type they are isomorphic to once given a parameter:
[[F + F']] a = Either ([[F]] a) ([[F']] a)
[[F * F']] a = ([[F]] a, [[F']] a)
[[F -> F']] a = [[F]] a -> [[F']] a
[[F . F']] a = [[F]] ([[F']] a)
[[Id]] a = a
[[Const X]] a = X
Now we can give our two algorithms. The first bit you've already written yourself:
fmap #(F + F') f (Left x) = Left (fmap #F f x)
fmap #(F + F') f (Right x) = Right (fmap #F' f x)
fmap #(F * F') f (x, y) = (fmap #F f x, fmap #F f y)
fmap #(Id) f x = f x
fmap #(Const X) f x = x
These correspond to the clauses you gave in your first instance. Then, in your [Graph a] example, you gave a clause corresponding to this:
fmap #(F . F') f x = fmap #F (fmap #F' f) x
That's fine, but this is also the first moment where we get some nondeterminism. One way to make this a functor is indeed nested fmaps; but another way is nested contramaps.
fmap #(F . F') f x = contramap #F (contramap #F' f) x
If both clauses are possible, then there are no Ids in either F or F', so both instances will return x unchanged.
The only thing left now is the arrow case, the one you ask about. But it turns out it's very easy in this formalism, there is only one choice:
fmap #(F -> F') f x = fmap #F' f . x . contramap #F f
That's the whole algorithm, in full detail, for defining the natural fmap. ...except one detail, which is the algorithm for the natural contramap. But hopefully if you followed all of the above, you can reproduce that algorithm yourself. I encourage you to give it a shot, then check your answers against mine below.
contramap #(F + F') f (Left x) = Left (contramap #F f x)
contramap #(F + F') f (Right x) = Right (contramap #F' f x)
contramap #(F * F') f (x, y) = (contramap #F f x, contramap #F' f y)
contramap #(F -> F') f x = contramap #F' f . x . fmap #F f
contramap #(F . F') f x = contramap #F (fmap #F' f) x
-- OR
contramap #(F . F') f x = fmap #F (contramap #F' f) x
-- contramap #(Id) fails
contramap #(Const X) f x = x
One thing of interest to me personally: it turns out that contramap #(Id) is the only leaf case that fails. All further failures are inductive failures ultimately deriving from this one -- a fact I had never thought of before! (The dual statement is that it turns out that fmap #(Id) is the only leaf case that actually uses its first function argument.)

Related

Does a joined Bitraversable require Monad?

Despite the jargon filled title I don't think this question is very complex.
Introducing the characters
There are two important Functor combinators at play here. Flip equivalent to the haskell functiong flip but operating on types
newtype Flip p a b
= Flip
{ unFlip :: p b a
}
and Join equivalent to the W combinator on types, it takes a bifunctor and produces a functor along both its arguments
newtype Join p a
= W
{ unW :: p a a
}
Traversable
Now for Foldable it is possible to make the following instance:
instance
( forall a . Foldable (p a)
, forall a . Foldable (Flip p a)
)
=> Foldable (Join p) where
foldr g x (W xs) = foldr g (foldr g x xs) (Flip xs)
That is to say if p is foldable across both of its arguments then Join p is foldable. This is done by folding across the left and then the right.
Now I would like to make an analogous instance for Traversable, however I run into a problem. I can write sequence easily enough
sequence (W xs) = (map W . join . map (sequenceA . unFlip) . sequenceA . Flip) xs
However it seems that I need to be able to use join so I am having trouble writing sequenceA. In fact it very much seems impossible to write a sequenceA.
However I struggle to come up with a counter example. That is a p which is traversable on two arguments but not traversable when joined.
So far I've tried all the basics but none are counter examples. Join (,) is traversable
sequenceA (W (x, y)) = liftA2 (W . (,)) x y
Higher order tuples such as Join ((,,) a) are fine.
sequenceA (W (x, y, z)) = liftA2 (W . (,,) x) y z
Join Either is also traversable
sequenceA (W (Left x)) = map (W . Left) x
sequenceA (W (Right x)) = map (W . Right) x
I've come up with more examples by composing types around, which I will leave out for simplicity but needless to say they all ended up being traversable.
Is there a counter example? Can this instance be written?

Applicative functor evaluation is not clear to me

I am currently reading Learn You a Haskell for Great Good! and am stumbling on the explanation for the evaluation of a certain code block. I've read the explanations several times and am starting to doubt if even the author understands what this piece of code is doing.
ghci> (+) <$> (+3) <*> (*100) $ 5
508
An applicative functor applies a function in some context to a value in some context to get some result in some context. I have spent a few hours studying this code block and have come up with a few explanations for how this expression is evaluated, and none of them are satisfactory. I understand that (5+3)+(5*100) is 508, but the problem is getting to this expression. Does anyone have a clear explanation for this piece of code?
The other two answers have given the detail of how this is calculated - but I thought I might chime in with a more "intuitive" answer to explain how, without going through a detailed calculation, one can "see" that the result must be 508.
As you implied, every Applicative (in fact, even every Functor) can be viewed as a particular kind of "context" which holds values of a given type. As simple examples:
Maybe a is a context in which a value of type a might exist, but might not (usually the result of a computation which may fail for some reason)
[a] is a context which can hold zero or more values of type a, with no upper limit on the number - representing all possible outcomes of a particular computation
IO a is a context in which a value of type a is available as a result of interacting with "the outside world" in some way. (OK that one isn't so simple...)
And, relevant to this example:
r -> a is a context in which a value of type a is available, but its particular value is not yet known, because it depends on some (as yet unknown) value of type r.
The Applicative methods can be very well understood on the basis of values in such contexts. pure embeds an "ordinary value" in a "default context" in which it behaves as closely as possible in that context to a "context-free" one. I won't go through this for each of the 4 examples above (most of them are very obvious), but I will note that for functions, pure = const - that is, a "pure value" a is represented by the function which always produces a no matter what the source value.
Rather than dwell on how <*> can best be described using the "context" metaphor though, I want to dwell on the particular expression:
f <$> a <*> b
where f is a function between 2 "pure values" and a and b are "values in a context". This expression in fact has a synonym as a function: liftA2. Although using the liftA2 function is generally considered less idiomatic than the "applicative style" using <$> and <*>, the name emphasies that the idea is to "lift" a function on "ordinary values" to one on "values in a context". And when thought of like this, I think it is usually very intuitive what this does, given a particular "context" (ie. a particular Applicative instance).
So the expression:
(+) <$> a <*> b
for values a and b of type say f Int for an Applicative f, behaves as follows for different instances f:
if f = Maybe, then the result, if a and b are both Just values, is to add up the underlying values and wrap them in a Just. If either a or b is Nothing, then the whole expression is Nothing.
if f = [] (the list instance) then the above expression is a list containing all sums of the form a' + b' where a' is in a and b' is in b.
if f = IO, then the above expression is an IO action that performs all the I/O effects of a followed by those of b, and results in the sum of the Ints produced by those two actions.
So what, finally, does it do if f is the function instance? Since a and b are both functions describing how to get a given Int given an arbitrary (Int) input, it is natural that lifting the (+) function over them should be the function that, given an input, gets the result of both the a and b functions, and then adds the results.
And that is, of course, what it does - and the explicit route by which it does that has been very ably mapped out by the other answers. But the reason why it works out like that - indeed, the very reason we have the instance that f <*> g = \x -> f x (g x), which might otherwise seem rather arbitrary (although in actual fact it's one of the very few things, if not the only thing, that will type-check), is so that the instance matches the semantics of "values which depend on some as-yet-unknown other value, according to the given function". And in general, I would say it's often better to think "at a high level" like this than to be forced to go down to the low-level details of exactly how computations are performed. (Although I certainly don't want to downplay the importance of also being able to do the latter.)
[Actually, from a philosophical point of view, it might be more accurate to say that the definition is as it is just because it's the "natural" definition that type-checks, and that it's just happy coincidence that the instance then takes on such a nice "meaning". Mathematics is of course full of just such happy "coincidences" which turn out to have very deep reasons behind them.]
It is using the applicative instance for functions. Your code
(+) <$> (+3) <*> (*100) $ 5
is evaluated as
( (\a->\b->a+b) <$> (\c->c+3) <*> (\d->d*100) ) 5 -- f <$> g
( (\x -> (\a->\b->a+b) ((\c->c+3) x)) <*> (\d->d*100) ) 5 -- \x -> f (g x)
( (\x -> (\a->\b->a+b) (x+3)) <*> (\d->d*100) ) 5
( (\x -> \b -> (x+3)+b) <*> (\d->d*100) ) 5
( (\x->\b->(x+3)+b) <*> (\d->d*100) ) 5 -- f <*> g
(\y -> ((\x->\b->(x+3)+b) y) ((\d->d*100) y)) 5 -- \y -> (f y) (g y)
(\y -> (\b->(y+3)+b) (y*100)) 5
(\y -> (y+3)+(y*100)) 5
(5+3)+(5*100)
where <$> is fmap or just function composition ., and <*> is ap if you know how it behaves on monads.
Let us first take a look how fmap and (<*>) are defined for a function:
instance Functor ((->) r) where
fmap = (.)
instance Applicative ((->) a) where
pure = const
(<*>) f g x = f x (g x)
liftA2 q f g x = q (f x) (g x)
The expression we aim to evaluate is:
(+) <$> (+3) <*> (*100) $ 5
or more verbose:
((+) <$> (+3)) <*> (*100) $ 5
If we thus evaluate (<$>), which is an infix synonym for fmap, we thus see that this is equal to:
(+) . (+3)
so that means our expression is equivalent to:
((+) . (+3)) <*> (*100) $ 5
Next we can apply the sequential application. Here f is thus equal to (+) . (+3) and g is (*100). This thus means that we construct a function that looks like:
\x -> ((+) . (+3)) x ((*100) x)
We can now simplify this and rewrite this into:
\x -> ((+) (x+3)) ((*100) x)
and then rewrite it to:
\x -> (+) (x+3) ((*100) x)
We thus have constructed a function that looks like:
\x -> (x+3) + 100 * x
or simpler:
\x -> 101 * x + 3
If we then calculate:
(\x -> 101*x + 3) 5
then we of course obtain:
101 * 5 + 3
and thus:
505 + 3
which is the expected:
508
For any applicative,
a <$> b <*> c = liftA2 a b c
For functions,
liftA2 a b c x
= a (b x) (c x) -- by definition;
= (a . b) x (c x)
= ((a <$> b) <*> c) x
Thus
(+) <$> (+3) <*> (*100) $ 5
=
liftA2 (+) (+3) (*100) 5
=
(+) ((+3) 5) ((*100) 5)
=
(5+3) + (5*100)
(the long version of this answer follows.)
Pure math has no time. Pure Haskell has no time. Speaking in verbs ("applicative functor applies" etc.) can be confusing ("applies... when?...").
Instead, (<*>) is a combinator which combines a "computation" (denoted by an applicative functor) carrying a function (in the context of that type of computations) and a "computation" of the same type, carrying a value (in like context), into one combined "computation" that carries out the application of that function to that value (in such context).
"Computation" is used to contrast it with a pure Haskell "calculations" (after Philip Wadler's "Calculating is better than Scheming" paper, itself referring to David Turner's Kent Recursive Calculator language, one of predecessors of Miranda, the (main) predecessor of Haskell).
"Computations" might or might not be pure themselves, that's an orthogonal issue. But mainly what it means, is that "computations" embody a generalized function call protocol. They might "do" something in addition to / as part of / carrying out the application of a function to its argument. Or in types,
( $ ) :: (a -> b) -> a -> b
(<$>) :: (a -> b) -> f a -> f b
(<*>) :: f (a -> b) -> f a -> f b
(=<<) :: (a -> f b) -> f a -> f b
With functions, the context is application (another one), and to recover the value -- be it a function or an argument -- the application to a common argument is to be performed.
(bear with me, we're almost there).
The pattern a <$> b <*> c is also expressible as liftA2 a b c. And so, the "functions" applicative functor "computation" type is defined by
liftA2 h x y s = let x' = x s -- embellished application of h to x and y
y' = y s in -- in context of functions, or Reader
h x' y'
-- liftA2 h x y = let x' = x -- non-embellished application, or Identity
-- y' = y in
-- h x' y'
-- liftA2 h x y s = let (x',s') = x s -- embellished application of h to x and y
-- (y',s'') = y s' in -- in context of
-- (h x' y', s'') -- state-passing computations, or State
-- liftA2 h x y = let (x',w) = x -- embellished application of h to x and y
-- (y',w') = y in -- in context of
-- (h x' y', w++w') -- logging computations, or Writer
-- liftA2 h x y = [h x' y' | -- embellished application of h to x and y
-- x' <- x, -- in context of
-- y' <- y ] -- nondeterministic computations, or List
-- ( and for Monads we define `liftBind h x k =` and replace `y` with `k x'`
-- in the bodies of the above combinators; then liftA2 becomes liftBind: )
-- liftA2 :: (a -> b -> c) -> f a -> f b -> f c
-- liftBind :: (a -> b -> c) -> f a -> (a -> f b) -> f c
-- (>>=) = liftBind (\a b -> b) :: f a -> (a -> f b) -> f b
And in fact all the above snippets can be just written with ApplicativeDo as liftA2 h x y = do { x' <- x ; y' <- y ; pure (h x' y') } or even more intuitively as
liftA2 h x y = [h x' y' | x' <- x, y' <- y], with Monad Comprehensions, since all the above computation types are monads as well as applicative functors. This shows by the way that (<*>) = liftA2 ($), which one might find illuminating as well.
Indeed,
> :t let liftA2 h x y r = h (x r) (y r) in liftA2
:: (a -> b -> c) -> (t -> a) -> (t -> b) -> (t -> c)
> :t liftA2 -- the built-in one
liftA2 :: Applicative f => (a -> b -> c) -> f a -> f b -> f c
i.e. the types match when we take f a ~ (t -> a) ~ (->) t a, i.e. f ~ (->) t.
And so, we're already there:
(+) <$> (+3) <*> (*100) $ 5
=
liftA2 (+) (+3) (*100) 5
=
(+) ((+3) 5) ((*100) 5)
=
(+) (5+3) (5*100)
=
(5+3) + (5*100)
It's just how liftA2 is defined for this type, Applicative ((->) t) => ...:
instance Applicative ((->) t) where
pure x t = x
liftA2 h x y t = h (x t) (y t)
There's no need to define (<*>). The source code says:
Minimal complete definition
pure, ((<*>) | liftA2)
So now you've been wanting to ask for a long time, why is it that a <$> b <*> c is equivalent to liftA2 a b c?
The short answer is, it just is. One can be defined in terms of the other -- i.e. (<*>) can be defined via liftA2,
g <*> x = liftA2 id g x -- i.e. (<*>) = liftA2 id = liftA2 ($)
-- (g <*> x) t = liftA2 id g x t
-- = id (g t) (x t)
-- = (id . g) t (x t) -- = (id <$> g <*> x) t
-- = g t (x t)
(which is exactly as it is defined in the source),
and it is a law that every Applicative Functor must follow, that h <$> g = pure h <*> g.
Lastly,
liftA2 h g x == pure h <*> g <*> x
-- h g x == (h g) x
because <*> associates to the left: it is infixl 4 <*>.

Is `data PoE a = Empty | Pair a a` a monad?

This question comes from this answer in
example of a functor that is Applicative but not a Monad:
It is claimed that the
data PoE a = Empty | Pair a a deriving (Functor,Eq)
cannot have a monad instance, but I fail to see that with:
instance Applicative PoE where
pure x = Pair x x
Pair f g <*> Pair x y = Pair (f x) (g y)
_ <*> _ = Empty
instance Monad PoE where
Empty >>= _ = Empty
Pair x y >>= f = case (f x, f y) of
(Pair x' _,Pair _ y') -> Pair x' y'
_ -> Empty
The actual reason why I believe this to be a monad is that it is isomorphic to Maybe (Pair a) with Pair a = P a a. They are both monads, both traversables so their composition should form a monad, too. Oh, I just found out not always.
Which counter-example failes which monad law? (and how to find that out systematically?)
edit: I did not expect such an interest in this question. Now I have to make up my mind if I accept the best example or the best answer to the "systematically" part.
Meanwhile, I want to visualize how join works for the simpler Pair a = P a a:
P
________/ \________
/ \
P P
/ \ / \
1 2 3 4
it always take the outer path, yielding P 1 4, more commonly known as a diagonal in a matrix representation. For monad associativy I need three dimensions, a tree visualization works better. Taken from chi's answer, this is the failing example for join, and how I can comprehend it.
Pair
_________/\_________
/ \
Pair Pair
/\ /\
/ \ / \
Pair Empty Empty Pair
/\ /\
1 2 3 4
Now you do the join . fmap join by collapsing the lower levels first, for join . join collapse from the root.
Apparently, it is not a monad. One of the monad "join" laws is
join . join = join . fmap join
Hence, according to the law above, these two outputs should be equal, but they are not.
main :: IO ()
main = do
let x = Pair (Pair (Pair 1 2) Empty) (Pair Empty (Pair 7 8))
print (join . join $ x)
-- output: Pair 1 8
print (join . fmap join $ x)
-- output: Empty
The problem is that
join x = Pair (Pair 1 2) (Pair 7 8)
fmap join x = Pair Empty Empty
Performing an additional join on those does not make them equal.
how to find that out systematically?
join . join has type m (m (m a)) -> m (m a), so I started with a triple-nested Pair-of-Pair-of-Pair, using numbers 1..8. That worked fine. Then, I tried to insert some Empty inside, and quickly found the counterexample above.
This approach was possible since a m (m (m Int)) only contains a finite amount of integers inside, and we only have constructors Pair and Empty to try.
For these checks, I find the join law easier to test than, say, associativity of >>=.
QuickCheck immediately finds a counterexample to associativity.
{-# LANGUAGE DeriveFunctor #-}
import Test.QuickCheck
data PoE a = Empty | Pair a a deriving (Functor,Eq, Show)
instance Applicative PoE where
pure x = Pair x x
Pair f g <*> Pair x y = Pair (f x) (g y)
_ <*> _ = Empty
instance Monad PoE where
Empty >>= _ = Empty
Pair x y >>= f = case (f x, f y) of
(Pair x' _,Pair _ y') -> Pair x' y'
_ -> Empty
instance Arbitrary a => Arbitrary (PoE a) where
arbitrary = oneof [pure Empty, Pair <$> arbitrary <*> arbitrary]
prop_assoc :: PoE Bool -> (Bool -> PoE Bool) -> (Bool -> PoE Bool) -> Property
prop_assoc m k h =
((m >>= k) >>= h) === (m >>= (\a -> k a >>= h))
main = do
quickCheck $ \m (Fn k) (Fn h) -> prop_assoc m k h
Output:
*** Failed! Falsifiable (after 35 tests and 3 shrinks):
Pair True False
{False->Pair False False, True->Pair False True, _->Empty}
{False->Pair False True, _->Empty}
Pair False True /= Empty
Since you are interested in how to do it systematically, here's how I found a counterexample with quickcheck:
{-# LANGUAGE DeriveFunctor #-}
import Control.Monad ((>=>))
import Test.QuickCheck
-- <your code>
Defining an arbitrary instance to generate random PoEs.
instance (Arbitrary a) => Arbitrary (PoE a) where
arbitrary = do
emptyq <- arbitrary
if emptyq
then return Empty
else Pair <$> arbitrary <*> arbitrary
And tests for the monad laws:
prop_right_id m = (m >>= return) == m
where
_types = (m :: PoE Int)
prop_left_id fun x = (return x >>= f) == f x
where
_types = fun :: Fun Int (PoE Int)
f = applyFun fun
prop_assoc fun gun hun x = (f >=> (g >=> h)) x == ((f >=> g) >=> h) x
where
_types = (fun :: Fun Int (PoE Int),
gun :: Fun Int (PoE Int),
hun :: Fun Int (PoE Int),
x :: Int)
f = applyFun fun
g = applyFun gun
h = applyFun hun
I don't get any failures for the identity laws, but prop_assoc does generate a counterexample:
ghci> quickCheck prop_assoc
*** Failed! Falsifiable (after 7 tests and 36 shrinks):
{6->Pair 1 (-1), _->Empty}
{-1->Pair (-3) (-4), 1->Pair (-1) (-2), _->Empty}
{-3->Empty, _->Pair (-2) (-4)}
6
Not that it's terribly helpful for understanding why the failure occurs, it does give you a place to start. If we look carefully, we see that we are passing (-3) and (-2) to the third function; (-3) maps to Empty and (-2) maps to a Pair, so we can't defer to the laws of either of the two monads PoE is composed of.
This kind of potential Monad instance can be concisely described as "taking the diagonal". It is easier to see why if we use the join presentation. Here is join for the Pair type you mention:
join (P (P a00 a11) (P a10 a11)) = P a00 a11
Taking the diagonal, however, is only guaranteed to give a lawful join for fixed length (or infinite) lists. That's because of the associativity law:
join . join = join . fmap join
If the n-th list in a list of lists doesn't have an n-th element, it will lead to the diagonal being trimmed: it will end before its n-th element. join . join takes the outer diagonal (of a list of lists of lists) first, while join . fmap join takes the inner diagonals first. It may be possible for an insufficiently long innermost list which is not in the outer diagonal to trim join . fmap join, but it can't possibly affect join . join. (This would be easier to show with a picture instead of words.)
Your PoE is a list-like type that doesn't have fixed length (the length is either zero or two). It turns out that taking its diagonal doesn't give us a monad, as the potential issue discussed above actually gets in the way (as illustrated in chi's answer).
Additional notes:
This is precisely the reason ZipList is not a monad: the zippy behaviour amounts to taking the diagonal.
Infinite lists are isomorphic to functions from the naturals, and fixed length lists are isomorphic to functions from the naturals up to an appropriate value. This means you can get a Monad instance for them out of the instance for functions -- and the instance you get, again, amounts to taking the diagonal.
Once upon a time I got confused about this exact issue.
(Posting this as a separate answer, as it has little overlap with my other one.)
The actual reason why I believe this to be a monad is that it is isomorphic to Maybe (Pair a) with Pair a = P a a. They are both monads, both traversables so their composition should form a monad, too. Oh, I just found out not always.
The conditions for the composition of monads m-over-n with n traversable are:
-- Using TypeApplications notation to make the layers easier to track.
sequenceA #n #m . pure #n = fmap #m (pure #n)
sequenceA #n #m . fmap #n (join #m)
= join #m . fmap #m (sequenceA #n #m) . sequenceA #n #m
sequenceA #n #m . join #n
= fmap #m (join #n) . sequenceA #n #m . fmap #n (sequenceA #n #m)
(There is also sequenceA #n #m . fmap #n (pure #m) = pure #m, but that always holds.)
In our case, we have m ~ Maybe and n ~ Pair. The relevant method definitions for Pair would be:
fmap f (P x y) = P (f x) (f y)
pure x = P x x
P f g <*> P x y = P (f x) (g y)
join (P (P a00 a01) (P a10 a11)) = P a00 a11 -- Let's pretend join is a method.
sequenceA (P x y) = P <$> x <*> y
Let's check the third property:
sequenceA #n #m . join #n
= fmap #m (join #n) . sequenceA #n #m . fmap #n (sequenceA #n #m)
-- LHS
sequenceA . join $ P (P a00 a01) (P a10 a11)
sequenceA $ P a00 a11
P <$> a00 <*> a11 -- Maybe (Pair a)
-- RHS
fmap join . sequenceA . fmap sequenceA $ P (P a00 a01) (P a10 a11)
fmap join . sequenceA $ P (P <$> a00 <*> a01) (P <$> a10 <*> a11)
fmap join $ P <$> (P <$> a00 <*> a01) <*> (P <$> a10 <*> a11)
fmap join $ (\x y z w -> P (P x y) (P z w)) <$> a00 <*> a01 <*> a10 <*> a11
(\x _ _ w -> P x w) <$> a00 <*> a01 <*> a10 <*> a11 -- Maybe (Pair a)
These are clearly not the same: while any a values will be drawn exclusively from a00 and a11, the effects of a01 and a10 are ignored in the left-hand side, but not in the right-hand side (in other words, if a01 or a10 are Nothing, the RHS will be Nothing, but the LHS won't necessarily be so). The LHS corresponds exactly to the vanishing Empty in chi's answer, and the RHS corresponds to the inner diagonal trimming described in my other answer.
P.S.: I forgot to show that the would-be instance we are talking about here is the same one being discussed in the question:
join' :: m (n (m (n a))) -> m (n a)
join' = fmap #m (join #n) . join #m . fmap #m (sequenceA #n #m)
With m ~ Maybe and n ~ Pair, we have:
join' :: Maybe (Pair (Maybe (Pair a))) -> Maybe (Pair a)
join' = fmap #Maybe (join #Pair) . join #Maybe . fmap #Maybe (sequenceA #Pair #Maybe)
join #Maybe . fmap #Maybe (sequenceA #Pair #Maybe) means the join' will result in Nothing unless there are no Nothings anywhere:
join' = \case
Just (P (Just (P a00 a01)) (Just (P a10 a11))) -> _
_ -> Nothing
Working out the non-Nothing case is straightforward:
fmap join . join . fmap sequenceA $ Just (P (Just (P a00 a01)) (Just (P a10 a11)))
fmap join . join $ Just (Just (P (P a00 a01) (P a10 a11)))
fmap join $ Just (P (P a00 a01) (P a10 a11))
Just (P a00 a11)
Therefore...
join' = \case
Just (P (Just (P a00 _)) (Just (P _ a11))) -> Just (P a00 a11)
_ -> Nothing
... which is essentially the same as:
join = \case
Pair (Pair a00 _) (Pair _ a11) -> Pair (a00 a11)
_ -> Empty

Is there a nicer way to apply a function to both elements of a pair in a list than a list comprehension?

I use this a fair bit:
a' = [ (f x, f y) | (x, y) <- a ]
Is there a better way to do that?
You can use the (***) operator from Control.Arrow
> map (f *** f) a
or define your own helper function
> let both f (x, y) = (f x, f y)
> map (both f) a
Alternative solution:
import Data.Bifunctor
bimap f f pair
Bifunctor.bimap is basically the same as Arrow.(***), but works for other bifunctors (like Either a b), too.
Digression:
The reason why there is nothing predefined for your case is that you can't write instances of Functor, Applicative etc for (,) having the same element type twice. With an own "vector-like" type you wouldn't have this problem:
data Pair a = Pair a a deriving Show
instance Functor Pair where
fmap f (Pair x y) = Pair (f x) (f y)
Now you can write things like map (fmap (+1)) [Pair 12 14, Pair 17 18]. Or if you want to use different operations on your Pair, you can go one step further:
instance Applicative Pair where
pure x = Pair x x
(Pair f g) <*> (Pair x y) = Pair (f x) (g y)
If you work a lot with same-element-type pairs, it could be useful to switch from (,) to such a type.
If you use lens, you can use over both f, or both %~ f. This has the advantage of being more composable -- for example, if you have a pair of lists, you can use something like both.mapped +~ toUpper (:: ([Char],[Char]) -> ([Char],[Char])).

Y Combinator in Haskell

Is it possible to write the Y Combinator in Haskell?
It seems like it would have an infinitely recursive type.
Y :: f -> b -> c
where f :: (f -> b -> c)
or something. Even a simple slightly factored factorial
factMaker _ 0 = 1
factMaker fn n = n * ((fn fn) (n -1)
{- to be called as
(factMaker factMaker) 5
-}
fails with "Occurs check: cannot construct the infinite type: t = t -> t2 -> t1"
(The Y combinator looks like this
(define Y
(lambda (X)
((lambda (procedure)
(X (lambda (arg) ((procedure procedure) arg))))
(lambda (procedure)
(X (lambda (arg) ((procedure procedure) arg)))))))
in scheme)
Or, more succinctly as
(λ (f) ((λ (x) (f (λ (a) ((x x) a))))
(λ (x) (f (λ (a) ((x x) a))))))
For the applicative order
And
(λ (f) ((λ (x) (f (x x)))
(λ (x) (f (x x)))))
Which is just a eta contraction away for the lazy version.
If you prefer short variable names.
Here's a non-recursive definition of the y-combinator in haskell:
newtype Mu a = Mu (Mu a -> a)
y f = (\h -> h $ Mu h) (\x -> f . (\(Mu g) -> g) x $ x)
hat tip
The Y combinator can't be typed using Hindley-Milner types, the polymorphic lambda calculus on which Haskell's type system is based. You can prove this by appeal to the rules of the type system.
I don't know if it's possible to type the Y combinator by giving it a higher-rank type. It would surprise me, but I don't have a proof that it's not possible. (The key would be to identify a suitably polymorphic type for the lambda-bound x.)
If you want a fixed-point operator in Haskell, you can define one very easily because in Haskell, let-binding has fixed-point semantics:
fix :: (a -> a) -> a
fix f = f (fix f)
You can use this in the usual way to define functions and even some finite or infinite data structures.
It is also possible to use functions on recursive types to implement fixed points.
If you're interested in programming with fixed points, you want to read Bruce McAdam's technical report That About Wraps it Up.
The canonical definition of the Y combinator is as follows:
y = \f -> (\x -> f (x x)) (\x -> f (x x))
But it doesn't type check in Haskell because of the x x, since it would require an infinite type:
x :: a -> b -- x is a function
x :: a -- x is applied to x
--------------------------------
a = a -> b -- infinite type
If the type system were to allow such recursive types, it would make type checking undecidable (prone to infinite loops).
But the Y combinator will work if you force it to typecheck, e.g. by using unsafeCoerce :: a -> b:
import Unsafe.Coerce
y :: (a -> a) -> a
y = \f -> (\x -> f (unsafeCoerce x x)) (\x -> f (unsafeCoerce x x))
main = putStrLn $ y ("circular reasoning works because " ++)
This is unsafe (obviously). rampion's answer demonstrates a safer way to write a fixpoint combinator in Haskell without using recursion.
Oh
this wiki page and
This Stack Overflow answer seem to answer my question.
I will write up more of an explanation later.
Now, I've found something interesting about that Mu type. Consider S = Mu Bool.
data S = S (S -> Bool)
If one treats S as a set and that equals sign as isomorphism, then the equation becomes
S ⇋ S -> Bool ⇋ Powerset(S)
So S is the set of sets that are isomorphic to their powerset!
But we know from Cantor's diagonal argument that the cardinality of Powerset(S) is always strictly greater than the cardinality of S, so they are never isomorphic.
I think this is why you can now define a fixed point operator, even though you can't without one.
Just to make rampion's code more readable:
-- Mu :: (Mu a -> a) -> Mu a
newtype Mu a = Mu (Mu a -> a)
w :: (Mu a -> a) -> a
w h = h (Mu h)
y :: (a -> a) -> a
y f = w (\(Mu x) -> f (w x))
-- y f = f . y f
in which w stands for the omega combinator w = \x -> x x, and y stands for the y combinator y = \f -> w . (f w).

Resources